No sharp line between the natural and the synthetic: biothetics and challenges to regulation (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
The code of human life stored in our cells is being extracted and transformed into biologically functional tissues at the same time it is also spawned with different synthetic materials that support those cells to mature and grow. Such products are essential of hybrid nature as they combine autologous and synthetic components, and thus making these products (that author labels as biothetics) difficult to categorize or put under existing know legal frameworks. This paper offers a brief review of the ethical, legal and social implications that regulators should be aware of. It also reflects on the bioconstitutional tensions that arise when novel technologies challenge the understanding of relations between our bodies, life and constitutions. By doing so, the paper examines the neoliberal underpinnings in the regulation of such a relationship.
Keywords: Bioprinting; biothetics; regulation; bioconstitutionalism; ELSI